Factors affecting the adoption of blockchain technologies in the food supply chain - Gcobisa Mbadlisa; Osden Jokonya (Frontiers in Sustainable Food Systems)
With the rise in food insecurity, one of the United Nation’s Sustainable Development Goals is to end hunger, achieve food security, and promote sustainable agriculture. This can be achieved through the strengthening and development of existing food systems. Integrating emerging technologies such as blockchain technology can help develop sustainable food systems. Blockchain technology allows the tracking and tracing of food items as they move through the supply chain. Blockchain technology also allows for low transactional costs at almost instantaneous applications. There is however a low adoption rate of blockchain technology amongst organisations in the food supply chain. The objective of the study was to explore factors that affect the adoption of blockchain technology in the food supply chain. The study adopted a quantitative research method that was guided by the technology, organisation, and environment Framework (TOE) to explore factors affecting blockchain technology adoption in the food supply chain. A systematic literature review was used for the study. Quantitative content analysis was used to analyse peer-reviewed articles. Results showed that TOE factors affect the adoption of blockchain technology in the food supply chain. Factors such as cost, scalability, firm size, and IT policy were noted as important factors affecting the adoption of blockchain technology in the food supply chain. The study contributes to the body of knowledge on factors that affect the adoption of blockchain technology in the food supply chain.